Coexisting chronic conditions associated with mortality and morbidity in adult patients with asthma. (April 2014) - Sumino, Kaharu; O'Brian, Katiuscia; Bartle, Brian; Au, David H.; Castro, Mario; Lee, Todd A.
Abstract Objective: Many asthma patients suffer from chronic conditions other than asthma. We investigated the specific contribution of common comorbidities on mortality and morbidity in adult asthma. Methods: In an observational study of adults with incident asthma identified between 1999 and 2003 using National Veterans Affairs and Centers for Medicare and Medicaid Services encounter databases (n = 25 975, follow-up 3.0 ± 1.7 years), association between 13 most prevalent comorbidities (hypertension, ischemic heart disease (IHD), osteoarthritis, rheumatoid arthritis, diabetes, mental disorders, substance/drug abuse, enlarged prostate, depression, cancer, alcoholism, HIV and heart failure) and four conditions previously associated with asthma (sleep apnea, gastroesophageal reflux disease (GERD), rhinitis and sinusitis) and mortality, hospitalizations and asthma exacerbations were assessed using multivariate regression analyses adjusted for other clinically important covariates. Results: HIV followed by alcoholism and mental disorders among 18–45-years old, and heart failure, diabetes, IHD and cancer among those ≥65 years old were associated with an increased risk of all-cause mortality. Many conditions were associated with increased risk for all-cause hospitalizations, but the increased risk was consistent across all ages for mental disorders. For asthma exacerbations, mental disorder followed by substance abuse and IHD were associated with increased risk among those 18–45 years old, and chronic sinusitis, mental disorder and IHD among those ≥65-years old. GERD was associated with decreased risk for asthma exacerbation in all ages. Conclusions: Many comorbidities are associated with poor outcome in adult asthmatics and their effect differs by age. Mental disorders are associated with increased risk of mortality and morbidity across ages.